Reasoning : a social picture - Laden, Anthony Simon, 1967- (Oxford : Oxford University Press, 2012)
Anthony Simon Laden explores the kind of reasoning we engage in when we live together: when we are responsive to others and neither commanding nor deferring to them. He argues for a new social picture of the activity of reasoning, in which reasoning is a species of conversation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Reasoning